Integrative analysis of morphological, transcriptomic, and metabolomic approaches to uncover the function of flavonoids in the salt stress response of Alhagi camelorum - Tang, Gangliang; Long, Lanlan; Li, Xiangyi; Guo, Xiaoxue; Lu, Mengxiao; Zeng, Fanjiang; Muhammad, Noor; Zhang, Bo (Frontiers in Plant Science, 2026)
Salinity or salt stress significantly influences plant productivity, growth, and development, including that of Alhagi camelorum. In the current study, transcriptomic characterization discovered DEGs among the samples of four paired groups. During the metabolomic profiling, the top ten identified primary metabolites are amino acids and their derivatives, fatty acids, alcohols and amines, lipids, GP, heterocyclic compounds, and flavonoids. An analysis of comparative metabolic pathways and KEGG enrichment indicated that salt stress disrupts the biosynthesis of sesquiterpenoids, triterpenoids, and diterpenoids, as well as the metabolism of phenylalanine, etc. Notably, the pathways associated with flavonoid biosynthesis, including genes such as (Asp04G007070, Asp04G008880, Asp06G017850, Asp02G032990, Asp05G012840, Asp03G022990, Asp05G008310, Asp05G006550) were identified as the most significant key genes. These findings underscore the molecular mechanisms involved in the salt response of A. camelorum, which could be employed in conservation programs for A. camelorum to enhance its tolerance to saline conditions.